Does Public Debt Moderate the Effect of Inflation Rate on Securities Market Returns in Kenya? - Kapchanga, David John; Owili, Poti Abaja; Onyuma, Samuel Owino (International Journal of Scientific Research and Management (IJSRM), 2018)
While in the last one two decades, Kenya has witnessed increasing levels of public borrowing, both domestic and foreign, economic growth has slowed down and the performance of the securities market has been subdued with falling stock prices. This has prompted stock investors to review and/or realign their investment portfolios. While the inflation rate has been drastically fluctuating, public debt – which is strongly inflationary – has had an exponential increase of about 461 percent between 2008 and 2018. Although Kenya’s level of public debt is approaching unsustainable levels, massive borrowing still continues. Using secondary monthly data obtained from government and securities market databases, this paper analyzed whether public debt moderates the relationship between inflation rate and securities market returns at the Nairobi Securities Exchange. Time series multiple linear regression results show that whereas inflation rate has a statistically significant negative effect on securities market returns, public debt had an insignificant negative effect on securities market returns. More importantly, public debt does not statistically affect the relationship between inflation rate and the securities market in Kenya. Putting in place strategies aimed at reducing inflation as well as public debt can however have the effect of improving securities market performance.